Profil Sosial Ekonomi Usaha Penganyam Daun Kelapa (Klangsah) di Kecamatan Abiansemal Kabupaten Badung - I MADE PUJA ASTAWA; I G. A. A. AMBARAWATI; A. A. A. WULANDIRA SAWITRI DJELANTIK (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Socio-Economic Profile of Coconut Leaf Weaver (Klangsah) in Abiansemal District, Badung Regency One example of the use of coconut leaves in Bali is klangsah. Klangsah are plaits made from old coconut leaves. Klangsah is used as a substitute for the roof in tents for traditional activities in Bali.The activity of weaving coconut leaves (klangsah) can provide job opportunities for the Balinese people. This research was conducted at the klangsah weaver business in Abiansemal District with the aim of knowing the socio-economic profile of the klangsah weavers and the income level of the klangsah weavers.The selection of the location was done intentionally and the selection of respondents was carried out by census, namely 18 klangsah weavers in Abiansemal District.The data analysis technique used in this research is descriptive qualitative analysis and descriptive quantitative analysis.The results showed that the social profile of the klangsah weavers in Abiansemal District according to their identity, all of the klangsah weavers were productive age with low education with the majority of women as business owners. Meanwhile, the economic profile of the klangsah weavers in Abiansemal District when viewed from (1) the business network, where the origin of the supply of raw materials comes from collectors in Jembrana Regency and farmers around the business location, (2) business characteristics, where the capital owned comes from loan funds and personal funds assisted by family workers and casual workers having an average number of working hours of 7 hours per day, (3) income, in 2020 the total income of klangsah weavers is Rp29.881.003.